Effective exchange rate volatility and its effect on tourism demand in India: a cointegration analysis - Bhatia, Arun; Singh, Kamal; Naik, Vinod (Anais Brasileiros de Estudos Turísticos, 2024)
Tourism has played a dominant role in the economy of the country since ancient times. Demand for tourism at the destination is a function of multiple variables like the level of domestic prices, the income of the tourists, foreign exchange rate, international price levels, cost of travel, etc. The relationship between effective exchange rates and foreign tourist arrivals in India is examined in the present study based on time series data of more than two decades. The results highlight that there exists a causal relationship between the exchange rate and foreign tourist arrivals in India. Further, if we wish to attract higher tourist footfall in the country, then along with increasing the level of investment in the tourism sector, policymakers need to manage the level of domestic prices in the country.